Economic history and the future of pedagogy in economics - Graham Brownlow; Christopher L. Colvin (Queen's University Centre for Economic History (QUCEH), 2022)
Economic history is integral to the study of economics and economies. Besides providing students with a valuable long-run perspective on the modern world, the field also helps them to better understand the contingency of economic theory. Despite a newfound interest in economic history among economists, teaching and learning in economic history at undergraduate level varies enormously across the UK. We review the different types of economic history provisioning in UK universities, account for the trends we document, and set out viable options for reform. We advance the idea that the teaching of economic history can be integrated into other higher-level undergraduate field courses, an approach we call "Teaching Economics With Economic History". We end by focusing on economic history teaching within the context of business schools.
Keywords: A22; B20; N01; 330; economic history; pedagogy; undergraduate curriculum